Strategy of the Kotabaru District Transportation Department in Implementing Parking E-Levy as Part of the Smart City Program - Nanda Laras Mukti; Budi Kristanto (Dinasti International Journal of Education Management and Social Science, 2025)
The implementation of electronic parking retribution (e-retribution) represents a digital innovation supporting the realization of Smart Governance and Smart Mobility at the local government level. This study aims to analyze the strategy and effectiveness of e-retribution implementation in Kotabaru Regency as part of the Smart City program. The research employed a descriptive qualitative approach, collecting data through in-depth interviews, field observations, and document analysis, and analyzed using the Miles, Huberman, and Saldaña (2023) interactive model. The findings reveal that e-retribution contributes positively to transparency, efficiency, and accountability in local revenue management. However, its effectiveness remains limited due to unequal digital infrastructure, low technological literacy, and weak inter-agency coordination. These challenges indicate the need for adaptive strategies and digital ecosystem strengthening to expand program success. This study contributes both empirically and theoretically to the development of Smart Governance and Smart Mobility concepts, particularly in the context of archipelagic local governments.